Islands or continents : International Poetry Nights in Hong Kong 2013 (Single Volume Anthology) - Dao, Bei (Islands or Continents., 2013)
Following the convening of International Poetry Nights in Hong Kong 2013, Islands or Continents is a collection of selected works by some of the most internationally acclaimed poets today. Included are the poems of Adonis (Syria), Aase Berg (Sweden), Conchitina Cruz (Philippines), Menna Elfyn (Wales), Lee Seong-bok (South Korea), Tim Lilburn (Canada), Zeyar Lynn (Myanmar), Dunya Mikhail (Iraq), Peter Minter (Australia), Tomasz Rózycki (Poland), Olvido García Valdes (Spain), Jeffrey Yang (USA), Raúl Zurita (Chile), as well as leading Chinese poets such as Natalia Chan, Han Dong, Lan Lan, Un Sio San, and Ye Mimi. The collection makes a treasured anthology of the finest contemporary poetry in trilingual or bilingual presentation.